Antibacterial effects of 70% ethanol and water extract of cacao beans (Theobroma cacao L.) on Aggregatibacter actinomycetemcomitans - Ayu Rafania Atikah; Hendrik Setia Budi; Tuti Kusumaningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) is a Gram negative bacteria that form a subgingival plaque causing periodontitis. Nowadays, many natural resources can be used as a basic ingredient of drugs. One of the resources used as an antibacterial material is cacao bean. It contains of polyphenol flavonoids, such as catechin, epicatechin, anthocyanin, and proanthocyanidin. Chemical compounds contained in ethanol extract and water extract are different in quantity from those in cocoa beans. Purpose: This research aimed to find out difference in antibacterial activity between the 70% ethanol and water extract of cacao beans (Theobroma cacao L.) on A. actinomycetemcomitans. Method: This research was an in vitro laboratory experiment. The serial dilutions was performed on the 70% ethanol and water extract of cacao beans a concentration of 100% to 3.125%. At each concentration, the 70% ethanol and water extract of cacao beans were added with grown bacterial suspension of A. actinomycetemcomitans. After they were incubated for 24 hours, the bacteria grown on Luria Berthani media were observed. Bacteria colonies then were measured in CFU/ml. Result: There were significant differences in bacterial colonies grown at the concentrations of 6.25% and 3.125% between the 70% ethanol extract of cacao beans and the water extract of cacao beans as p-value = 0.000 (p<0.05). Conclusion: 70% Ethanol beans and water extract of cacao beans have antibacterial activity against A. Actinomycetemcomitans. The concentrations of MIC and MBC extracts were 6.25% and 12.5% respectively.